On the boundedness and oscillation of solutions to (m(t)x′)′+a(t)b(x)=0 - Allan J. Kroopnick (International Journal of Mathematics and Mathematical Sciences)
In this paper, we discuss under what conditions the solutions to (m(t)x′)′+a(t)b(x)=0 are bounded, oscillatory, and stable. Furthermore, some applications of these results are given during the discussion and proofs of the theorems.